Correction to: Preconditioning of Human Decidua Basalis Mesenchymal Stem/Stromal Cells with Glucose Increased Their Engraftment and Anti-diabetic Properties - Yasser Basmaeil; Manar Al Rashid; Tanvir Khatlani; Manal AlShabibi; Eman Bahattab; Meshan L. Abdullah; Fawaz Abomaray; Bill Kalionis; Safia Massoudi; Mohamed Abumaree (Tissue Engineering and Regenerative Medicine, 2020)
The author would like to correct the names for the below co-authors in the online published article.

Preconditioning of Human Decidua Basalis Mesenchymal Stem/Stromal Cells with Glucose Increased Their Engraftment and Anti-diabetic Properties - Yasser Basmaeil; Manar Al Rashid; Tanvir Khatlani; Manal AlShabibi; Eman Bahattab; Meshan L. Abdullah; Fawaz Abumary; Bill Kalionis; Safia Massoudi; Mohammad AbuMaree (Tissue Engineering and Regenerative Medicine, 2020)
Background: Mesenchymal stem/stromal cells (MSCs) from the decidua basalis (DBMSCs) of the human placenta have important functions that make them potential candidates for cellular therapy. Previously, we showed that DBMSC functions do not change significantly in a high oxidative stress environment, which was induced by hydrogen peroxide (H 2 O 2 ) and immune cells. Here, we studied the consequences of glucose, another oxidative stress inducer, on the phenotypic and functional changes in DBMSCs. Methods: DBMSCs were exposed to a high level of glucose, and its effect on DBMSC phenotypic and functional properties was determined. DBMSC expression of oxidative stress and immune molecules after exposure to glucose were also identified. Results: Conditioning of DBMSCs with glucose improved their adhesion and invasion. Glucose also increased DBMSC expression of genes with survival, proliferation, migration, invasion, anti-inflammatory, anti-chemoattractant and antimicrobial properties. In addition, DBMSC expression of B7H4, an inhibitor of T cell proliferation was also enhanced by glucose. Interestingly, glucose modulated DBMSC expression of genes involved in insulin secretion and prevention of diabetes. Conclusion: These data show the potentially beneficial effects of glucose on DBMSC functions. Preconditioning of DBMSCs with glucose may therefore be a rational strategy for increasing their therapeutic potential by enhancing their engraftment efficiency. In addition, glucose may program DBMSCs into insulin producing cells with ability to counteract inflammation and infection associated with diabetes. However, future in vitro and in vivo studies are essential to investigate the findings of this study further.

Current Status and Future Challenges of Weather Radar Polarimetry: Bridging the Gap between Radar Meteorology/Hydrology/Engineering and Numerical Weather Prediction - Guifu Zhang; Vivek N. Mahale; Bryan J. Putnam; Youcun Qi; Qing Cao; Andrew D. Byrd; Petar Bukovcic; Dusan S. Zrnic; Jidong Gao; Ming Xue; Youngsun Jung; Heather D. Reeves; et al. (Advances in Atmospheric Sciences, 2019)